2019
DOI: 10.48550/arxiv.1904.05358
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Gemini Planet Imager Exoplanet Survey: Giant Planet and Brown Dwarf Demographics From 10-100 AU

Eric L. Nielsen,
Robert J. De Rosa,
Bruce Macintosh
et al.

Abstract: We present a statistical analysis of the first 300 stars observed by the Gemini Planet Imager Exoplanet Survey (GPIES). This subsample includes six detected planets and three brown dwarfs; from these detections and our contrast curves we infer the underlying distributions of substellar companions with respect to their mass, semi-major axis, and host stellar mass. We uncover a strong correlation between planet occurrence rate and host star mass, with stars M * > 1.5M more likely to host planets with masses betw… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 146 publications
(259 reference statements)
1
24
0
Order By: Relevance
“…Observations suggest that giant planets form more frequently around intermediate mass stars than around solar-mass stars (see e.g. Johnson et al 2010;Nielsen et al 2019). Herbig AeBe (HAeBe) stars (Herbig 1960;Hillenbrand et al 1992) are still embedded in gasdust envelopes and are frequently surrounded by circumstellar disks (Perez & Grady 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Observations suggest that giant planets form more frequently around intermediate mass stars than around solar-mass stars (see e.g. Johnson et al 2010;Nielsen et al 2019). Herbig AeBe (HAeBe) stars (Herbig 1960;Hillenbrand et al 1992) are still embedded in gasdust envelopes and are frequently surrounded by circumstellar disks (Perez & Grady 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence rate of massive companions from direct imaging surveys in older systems argues against brown dwarf companions as a common explanation for transition disks. Super-Jovians (5-13 M Jup ) have an occurrence rate of 8.9% at 10-100 au for intermediate mass (1.5-5 M ) stars (Nielsen et al 2019), which is the stellar mass range of the majority of our sample. Above that mass treshold, the occurrence rate of brown dwarfs (13-80 M Jup ) at wide orbits is much lower (∼1% Nielsen et al 2019, also known as the 'brown dwarf desert'), but the occurrence of stellar companions (> 80M Jup ) or binarity rate at 10-100 au is again increased, with a fraction of ∼15% in the 1-2 M stellar mass range (Moe & Kratter 2019).…”
Section: Implications For Companionsmentioning
confidence: 89%
“…Second-generation exoplanet imagers have already demonstrated great potential for studying close circumstellar environments, and for detecting new companions and helping to understand their physical properties. However, the current statistics derived from observations (e.g., Nielsen et al 2019) and the most recent planet population models (e.g., Mordasini et al 2017;Forgan et al 2018) respectively show and predict that giant planets are scarce in the regime of mass and separation probed by current instruments. In other words, we need to probe closer to the stars and at deeper contrasts.…”
Section: Discussionmentioning
confidence: 99%
“…These results begin to shed light on the architecture of planetary systems, planet formation and evolution, and atmospheric properties of young giant planets and brown dwarfs. In terms of planet demography, NIR surveys of hundreds of nearby stars have so far shown that giant gaseous planets on orbits wider than 10 AU remain rare, mostly due to inefficient formation of such companions at large distances (e.g., Bowler 2016;Uyama et al 2017;Vigan et al 2017;Chauvin et al 2017a;Nielsen et al 2019).…”
Section: Introductionmentioning
confidence: 99%